Towards green growth? : tracking progress. - Organisation for Economic Co-operation and Development (Paris : OECD Publishing, 2015)
This report attempts to evaluate the progress and highlight where there is broad scope to heighten the ambition and effectiveness of green growth policy. It draws lessons from green growth mainstreaming across the OECD's work programme, notably in terms of how governments can maximise institutional settings to seize economic opportunities surrounding the transition to a green economy, and considers ways to enrich the Green Growth Strategy based on work undertaken since its launch.
Foreword and acknowledgements -- Executive Summary -- A Framework to align economic and environmental goals -- Country efforts to implement green growth -- Revisiting the Green Growth Strategy -- The value of institutional settings for mainstreaming green growth -- Bibliography.
"Four Years of the Green Growth Strategy"--Cover.
Includes bibliographical references.
Keywords: Economic development -- Environmental aspects -- Evaluation; Sustainable development -- Evaluation; Environmental policy -- Economic aspects